The influence of salespeople and prices on repeat purchases mediated by service quality - Fresti Aldi; Budi Haryono; Melitina Tecualu (Institute of Computer Science (IOCS), 2023)
Repurchasing or repeat orders is consumer behavior in buying a particular product based on their experience. This experience will shape the consumer's decision to accept or reject a product after the consumer has tried it. The purpose of this study was to determine the influence of the sales force and price on repurchasing which is mediated by the quality of service to WOM Finance Semarang Branch consumers. The subjects of this study were companies and employees of WOM Finance Semarang Branch Company. The sampling technique in this study used purposive sampling. The instrument used in this research is a questionnaire. the analytical method used is the instrument used is the validity test and reliability test and hypothesis testing. The results of the following research are that salespeople have a positive and significant effect on repeat purchases, prices have a positive and significant effect on repeat purchases, salespeople have a positive and significant effect on service quality, prices have a positive and insignificant effect on service quality, service quality has a positive and significant effect on repeat purchases, service quality has a significant effect in mediating the relationship between salespeople and repeat purchases, and service quality has a significant effect in mediating the relationship between price and repeat purchases for WOM Finance Semarang Branch consumers.